2018
DOI: 10.1111/auar.12229
|View full text |Cite
|
Sign up to set email alerts
|

Local Government Audit Committees: A Behaviour Framework for Effective Audit Committee Performance

Abstract: Stakeholders will always be more receptive to the creation of structured and credible systems that pull participants towards good governance outcomes which serve to remove temptation rather than systems that attempt to push or otherwise coerce people into a state of compliance. This paper uses behavioural theory as an interpretative lens to explain the actions and effectiveness of public sector audit committees. Financial probity, independence to avoid conflicts of interest and conformance to ethical practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(181 reference statements)
1
4
0
1
Order By: Relevance
“…By combining descriptive results with the results from hypothesis two (H2) of this study which stated that there is a substantial association between AC weakness and FRM, the result shows that AC weakness is statistically insignificant and negatively related to FRM. This was also found in the earlier study by Thomas & Purcell (2019), who revealed that the AC with few weaknesses influences the effective management of financial resources in local government authorities. Moreover, the results of Soobaroyen (2014) were on effective AC in higher learning institutions; therefore, there is a positive influence on efficient resource management.…”
Section: The Relationship Between Ac and Frmsupporting
confidence: 79%
See 1 more Smart Citation
“…By combining descriptive results with the results from hypothesis two (H2) of this study which stated that there is a substantial association between AC weakness and FRM, the result shows that AC weakness is statistically insignificant and negatively related to FRM. This was also found in the earlier study by Thomas & Purcell (2019), who revealed that the AC with few weaknesses influences the effective management of financial resources in local government authorities. Moreover, the results of Soobaroyen (2014) were on effective AC in higher learning institutions; therefore, there is a positive influence on efficient resource management.…”
Section: The Relationship Between Ac and Frmsupporting
confidence: 79%
“…These results contrast with the study of Braunstein & Welch (2002) who show that public BICA are in the front line in managing their resources well compared to any other entities in the public services. This appeared to be true even in the current work of Thomas & Purcell (2019), which revealed that audit committees in LGAs are effective. This is because a huge number of resources are inverted into them.…”
Section: The Relationship Between Ac and Frmmentioning
confidence: 69%
“…Though improved housing would positively affect other programmes such as income generation and health, the nongovernment organization has yet to be widely involved in urban housing. Md Jahangir Alam explores changing land values in the rapid urbanization process in Dhaka, Bangladesh [8]. Its implications for urban land management and administration in the megacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, 47 articles among our sample rely on quantitative methods, 26 are conceptual papers and 11 are based on mixed methods. Only five articles are literature reviews (Bonollo, 2019;Hay and Cordery, 2018;Mbewu and Barac, 2017;Thomas and Purcell, 2019;Nerantzidis et al, 2020) and only one (Guthrie and Parker, 1999) uses an experimental method (see Figure 5).…”
Section: Trends Across the Publicationmentioning
confidence: 99%